Sistem Pakar Mendiagnosa Penyakit Pneumonia Menggunakan Metode Constraint Satisfaction Problem (CSP) - Putri, Wirda Ayu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
At this time the use of computer technology has grown rapidly among the community. Most people use it not only for commercial purposes, but also to get information on disease detection quickly and efficiently with computer-based applications that can help the general public to find out the causes and symptoms of the disease. For that, we need a system that is designed to be able to imitate the expertise of an expert in answering questions and solving a problem in accordance with the knowledge of an expert that is entered into a computer system. The development of artificial intelligence technology that has occurred has allowed expert systems to be applied in detecting diseases using programming languages. One of them is in providing information about various problems, especially pneumonia. The expert system method used is Constraint Satisfaction Problem (CSP) which is used to deal with uncertainty in the diagnosis of pneumonia. With the facilities provided to the user, it allows the user to use this system according to their respective needs. Users are given the convenience of knowing information about the symptoms of pneumonia, and its prevention.